PERENCANAAN STRATEGIS BERBASIS INKLUSI PADA PENINGKATAN AKSESIBILITAS DAN KENYAMANAN JALUR PEDESTRIAN BAGI TUNANETRA DI KAWASAN PEUNAYONG - T. Zainuddin, T. Zainuddin (Kybernology Jurnal Ilmu Pemerintahan dan Administrasi Publik, 2024)
The blind have not received optimal attention in the provision of public facilities, such as in Peunayong Area, Banda Aceh, which has limited provision of pedestrian paths. The purpose of this study is to formulate strategic planning in an effort to improve the accessibility of pedestrian paths for the blind to increase independence. This study was conducted with qualitative approach, the types of data used were primary and secondary data. Data were validated using source triangulation. Data were analyzed using SWOT and AHP. Results: 1) The Peunayong Area has limited pedestrian path that is not equipped with guiding blocks, unrecommended materials and suitable for blind people. The function of pedestrian path has changed into trade and illegal parking; 2) it is necessary to formulate strategic planning using SWOT analysis that produces combination of strength-opportunity strategies, several alternative strategy options are analyzed using AHP; 3) The priority strategy to solve the problem of accessibility for the blind is to conduct inclusion strategic planning. Strategic planning is implemented within 3 years, namely the planning stage includes the creation of universal and inclusive policies with collaborative governance approach, socialization and education; the implementation stage includes the construction of infrastructure, the return function of pedestrian paths, zoning of the Peunayong Area and continued socialization and education; the evaluation stage includes monitoring and evaluating success. Conclusion: the blind have the right to use public facilities to empower their quality and role in society, this is followed up with inclusion-based planning and policies.